# algebra

posted by .

find the indicated outputs for f(x = 3x^2 -5x

f(0)=
f(-1)=
f (2)=

• algebra -

Plug in x = 0 and compute f(x) using the formula given. In the first case:

3*0^2 - 5*0 = 0

Then do the same thing for x = -1 and x = 2.

## Similar Questions

1. ### Algebra 1

Find the indicated outputs for f(x)=4x(2)-5x f(0)=?
2. ### algebra

find the indicated outputs for f(x)= 4x-5x= f(0)= f(-1)= f(2)=
3. ### algebra

find the indicated outputs for f(x)= 4x^2- 5x= f(0)= f(-1)= f(2)=
4. ### Algebra

find the indicated outputs f(x)=2x^2-3x f(0)=?
5. ### algebra

Find the indicated outputs for f(x) = 2x(2) - 2x f(0), f(1), f(2)
6. ### Algebra

Find the indicated outputs for f(x)= 5 x(2) - 4x. F(0)= f(-1)= f(2)=
7. ### algebra

find the indicated outputs for f(x)5^2-4x F(0)= f(-1)= f(2)=
8. ### algebra

Find the indicated outputs for f(x)=4x^2 -4x f(0) f(-1) f(2)
9. ### algebra

Find the indicated outputs for f(x) =4x^2 -4x f(0) f(-1) f(2)
10. ### Algebra

Find the indicated outputs for f(x)=¡¼5x¡½^(2 )-2x f(0)= f(-1)= f(2)=

More Similar Questions